Penjernihan Air dengan Metode Rapid Sand Filter Menggunakan Zeolit dan Karbon Aktif Sebagai Adsorben di Kelurahan Lingkar Selatan, Kota Jambi. - Rahayu, Martina Asti; Utami, Andita; Wijaya, Dhian Eka; Permana, Edwin (Jurnal Pengabdian Masyarakat Pinang Masak, 2023)
The need for clean water for the citizens of Jambi City still remains a serious problem until now. Ironically, for the past five years, the difficulty of fulfilling the need for clean water in some areas of Jambi City is even more alarming. The supply of tap water to the citizen’s houses is still not smooth. So as an alternative, citizens use ground water as a source of water. However, the groundwater obtained is still cloudy and smelly, and the flow of water causes the formation of the crust on the bathroom wall. This will certainly hamper the productivity and the economy of the citizens. Efforts are needed to overcome this problem so that people can get clean water. In this program, conducted a counseling or socialization on the way of water treatment from well water. This community service program aims to share knowledge about how to conduct water purification process to the community so that citizens can consume clean water. In this program, performed demonstration of a simple water purifier using Rapid Sand Filter method in the presence of zeolite and activated carbon that will maximize the water purification process.